A concise economic history of Britain : from 1750 to recent times - Court, W. H. B. (Cambridge, Eng. : University Press, 1954)
The economic problems of men begin in the scarcities and inequalities of nature, although they may be sharpened beyond measure.
A sequel to Sir John Clapham's A concise economic history of Britain from the earliest times to A.D. 1750.
Includes index of references.
II 17/01/2019
Loans
Keywords: Economic history; Great Britain..